2012
DOI: 10.1128/mbio.00373-12
|View full text |Cite|
|
Sign up to set email alerts
|

Contrasting Life Strategies of Viruses that Infect Photo- and Heterotrophic Bacteria, as Revealed by Viral Tagging

Abstract: Ocean viruses are ubiquitous and abundant and play important roles in global biogeochemical cycles by means of their mortality, horizontal gene transfer, and manipulation of host metabolism. However, the obstacles involved in linking viruses to their hosts in a high-throughput manner bottlenecks our ability to understand virus-host interactions in complex communities. We have developed a method called viral tagging (VT), which combines mixtures of host cells and fluorescent viruses with flow cytometry. We inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
79
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(81 citation statements)
references
References 77 publications
2
79
0
Order By: Relevance
“…The present study demonstrated that ssDN A phage at the BATS site are quite diverse and display temporal patterns in community composition similar to those of dsDN A viruses. As a first step towards deciphering the ecological impact of ssDNA phage, future studies should attempt to link the ssDNA phage with their potential host communities, a task that will be greatly aided by emerging singlecell methods such as phageFISH and viral tagging (Deng et al 2012, Allers et al 2013, Dang & Sullivan 2014, Brum & Sullivan 2015. This study's goal was to obtain an overview of the viral communities over 2 depths, 2 seasons, and several years, by using 4 different methods.…”
Section: Resultsmentioning
confidence: 99%
“…The present study demonstrated that ssDN A phage at the BATS site are quite diverse and display temporal patterns in community composition similar to those of dsDN A viruses. As a first step towards deciphering the ecological impact of ssDNA phage, future studies should attempt to link the ssDNA phage with their potential host communities, a task that will be greatly aided by emerging singlecell methods such as phageFISH and viral tagging (Deng et al 2012, Allers et al 2013, Dang & Sullivan 2014, Brum & Sullivan 2015. This study's goal was to obtain an overview of the viral communities over 2 depths, 2 seasons, and several years, by using 4 different methods.…”
Section: Resultsmentioning
confidence: 99%
“…This has been applied to model systems (for example, marine Pseudoalteromonas and its phages) 102 , but is readily transferable to the field if knowledge of host and viral gene markers is available. Finally, viral tagging identifies phages that can infect a cultivated microbial host, and does not require the use of marker genes 103,104 (FIG. 3d).…”
Section: Quantitative Host Range Analysismentioning
confidence: 99%
“…The example shown here demonstrates the ability of phageFISH to detect different stages of infection. d | In viral tagging 103,104 , fluorescently stained wild viruses are mixed with cultivated microorganisms, allowing adsorption of viruses to their host. Cells are then sorted by flow cytometry to separate cells with and without attached viruses, and then metagenomic sequencing is used to assemble the genomes of viruses that infect the cultivated host microorganism.…”
Section: Virus-host Interactions: Expanding Diversitymentioning
confidence: 99%
“…In a similar approach, we have utilized the analysis of the CRISPR/ Cas loci derived from single cell genomics from archaeal dominated hot springs to link viral genomes detected by viral metagenomics to their hosts. Other approaches developed in marine systems such as viral tagging (Deng et al, 2012(Deng et al, , 2014b and FISH tools (Allers et al, 2013;Sheik et al, 2014) provide a direct and rapid means to link virus types to their hosts in natural systems. Further advances will likely result in the development of novel techniques to temporally monitor total virus infection in natural environments.…”
Section: Advance Cultivation and Molecular Techniques To Link Archaeamentioning
confidence: 99%